Citizens’ attitudes, concern and familiarity with animal production explaining the purchase intention for animal-welfare-labeled pork - Heinola, Katriina; Kaseva, Janne; Latvala, Terhi; Niemi, Jarkko Kristian (Scientific Agricultural Society of Finland, 2025)
This study uses a modified Theory of Planned Behavior (TPB) to explore how the ethical concern and familiarity with animal farming as proxies for self-identity and consumption strategies of ‘boycotting’ and ‘buycotting’, influence citizens’ intentions for purchasing and paying a premium for welfare-labeled pork. A survey was conducted with 400 Finnish respondents, and structural equation modeling was used to analyze the relationships within TPB constructs, including above-mentioned modifications of self-identity and consumption strategies, across different socioeconomic subgroups and the full sample. The findings indicate that attitudes toward farm animal welfare, ethical concerns, and familiarity with animal farming are the strongest predictors of purchasing intentions for welfare-labeled pork. While most respondents expressed a willingness to pay more for AW-labeled products, the role of boycotting emerged as more significant than buycotting, particularly among women and those sharing grocery shopping responsibilities. Social norms and perceived behavioral control showed limited influence in the full sample but were significant for specific groups, such as higher-educated consumers and middle-aged respondents. These results provide valuable insights into consumer motivations, particularly the role of self-identification with ethical concerns, and offer strategic opportunities for marketers and policymakers to promote ethical consumption and strengthen the market potential of welfare-labeled products.
Keywords: ethical consumption; theory of planned behavior; boycotting; buycotting